How the Professional Judgment Standard Could Undermine the Validity of Sexually Violent Predator Laws - David W. Nordsieck (Washington University Law Review, 2011)
The Article presents common features of the statutory schemes for the involuntary dedication of sexually violent predators in the U.S. in 2011. It examines several cases in the Supreme Court that shed some light on how the treatment that is offered to sexually violent predators might impact the constitutionality of their confinement. It discusses the consequences and proprietary of the professional judgment standard as a way to evaluate challenges to treatment.
Keywords: Kansas v. Hendricks 521 U.S. 346 (1997); Civil commitment; Due process of law; Sex offenders; United States